The next sustainability wave : building boardroom buy-in - Willard, Bob (New Society Publishers, 2005)
The idea of sustainability has been embraced enthusiastically by some businesses and rejected by others. The first wave of corporate converts to sustainability was driven by a PR crisis perhaps, regulatory pressures, or the founder's personal passion. The next wave, however, requires different drivers if it is to build a critical mass for corporate responsibility in the business community. The Next Sustainability Wave assesses why companies have resisted sustainability strategies and focuses on two emerging drivers that promise to spur corporate commitment to sustainability strategies.